2021
DOI: 10.37989/gumussagbil.889608
|View full text |Cite
|
Sign up to set email alerts
|

Y Kuşağı Bireylerin Sağlıklı Yaşam Farkındalık Düzeylerinin İncelenmesi

Abstract: Bu çalışmada Isparta il merkezinde ikamet eden Y kuşağı bireylerin sağlıklı yaşam farkındalık düzeylerinin çeşitli değişkenler açısından incelenmesi amaçlanmıştır. Araştırmaya kolayda örnekleme yöntemiyle Isparta ilinde ikamet eden 21-40 yaş aralığında 382 birey dahil edilmiştir. Katılımcılara sosyo-demografik özellikler ile Sağlıklı Yaşam Farkındalığı Ölçeği'ni (SYFÖ) içeren anket formu uygulanmıştır. Araştırmanın verileri t testi, ANOVA (F testi) ve Korelasyon analizi ile elde edilmiştir. Sağlıklı yaşam fark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
4
0
3
Order By: Relevance
“…Moreover, mothers who give formula or supplementary food to their babies experience problems with breastfeeding (Tanrıkulu et al, 2012;Jiang et al, 2022). Thus, it is not recommended to feed babies with formula or any other supplementary food (Yılmaz, 2019). It was found in our study that mothers using formula or supplementary food experienced more breastfeeding problems (p<0.05).…”
Section: Resultsmentioning
confidence: 55%
“…Moreover, mothers who give formula or supplementary food to their babies experience problems with breastfeeding (Tanrıkulu et al, 2012;Jiang et al, 2022). Thus, it is not recommended to feed babies with formula or any other supplementary food (Yılmaz, 2019). It was found in our study that mothers using formula or supplementary food experienced more breastfeeding problems (p<0.05).…”
Section: Resultsmentioning
confidence: 55%
“…[ 14 ] On the contrary, Yılmaz et al obtained no significant difference between gender and awareness of healthy living, but it was determined that the female gender had higher scores than males. [ 15 ] We found that the female gender has an independent positive effect on high HLA. In addition, we observed that age made a change in avoidance attitudes from COVID-19.…”
Section: Discussionmentioning
confidence: 83%
“…Bunun için de sağlıklı yaşamın farkında olmak gerekmektedir. Farkındalık, bireyin çevresini tanıması, anlaması ve yaptığı bir şeyi açıklayabilme becerisi olarak tanımlanmaktadır (Yılmaz ve Özer, 2021). Diğer bir ifade ile farkındalık, bilinmesi gerekli olan şeyler hakkında haberdar ve farkında olma durumu olarak tanımlanmaktadır (Türk Dil Kurumu Sözlükleri, 2011).…”
Section: Sağlıklı Yaşam Farkındalığı Kavramıunclassified
“…Diğer bir ifade ile farkındalık, bilinmesi gerekli olan şeyler hakkında haberdar ve farkında olma durumu olarak tanımlanmaktadır (Türk Dil Kurumu Sözlükleri, 2011). Farkındalık düzeyi yüksek kişiler, kendisine ve çevresine dair düzenlemeler yapabilen bilinçlilik düzeyleri de yüksek olan kişilerdir (Yılmaz ve Özer, 2021). Bilinçli farkındalık, bireyleri basmakalıplardan uzaklaştırarak sağlıklı ve bilinçli davranışlar sergilemeleri bakımından önemlidir (Özer ve Yılmaz, 2020).…”
Section: Sağlıklı Yaşam Farkındalığı Kavramıunclassified
See 1 more Smart Citation